2020
DOI: 10.1093/advances/nmaa082
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable and Fruit Consumption and Prognosis Among Cancer Survivors: A Systematic Review and Meta-Analysis of Cohort Studies

Abstract: The number of cancer survivors is growing rapidly worldwide, especially long-term survivors. Although a healthy diet with a high vegetable and fruit consumption is a key factor in primary cancer prevention, there is a lack of specific dietary recommendations for cancer survivors, except in the case of breast cancer [World Cancer Research Fund (WCRF)/American Institute for Cancer Research (AICR) report]. We have therefore carried out a systematic review and meta-analysis of cohort studies reporting on the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 90 publications
1
51
0
Order By: Relevance
“…Studies have shown differences in fruit consumption across the world based on the socioeconomic status, sex, and geographic location. From these studies, cancer incidence was estimated to decrease by 14% with consumption of 550-600 g of fruit and vegetable per day, which is greater than the current recommendations made by WHO [34,35]. These results suggest that a healthy diet such as one high in fruits and vegetables has protective effects against different types of cancer.…”
Section: Importance Of Phytochemicals From Diet In Management Of Cancermentioning
confidence: 89%
“…Studies have shown differences in fruit consumption across the world based on the socioeconomic status, sex, and geographic location. From these studies, cancer incidence was estimated to decrease by 14% with consumption of 550-600 g of fruit and vegetable per day, which is greater than the current recommendations made by WHO [34,35]. These results suggest that a healthy diet such as one high in fruits and vegetables has protective effects against different types of cancer.…”
Section: Importance Of Phytochemicals From Diet In Management Of Cancermentioning
confidence: 89%
“…In contrast, in another review, higher intake of vegetables was inversiley associated with overall mortality, though among cancer survivors only, at both cancer pre-and postdiagnosis [19]. Importantly, when considering cancer-specific mortality, it has been shown that intake of vegetables could reduce cancer mortaltiy in survivors of head and neck cancer and of ovarian cancer, but not other cancer types [80]. In the EPIC study, only a few cancer-specific associations were evaluated and, for instance, there was a non-significant association between intake of fruits and vegetables and mortality related to prostate cancer [35].…”
Section: Protective Factors Against Cancer Mortalitymentioning
confidence: 93%
“…Plants with a variety of bioactive compounds and antioxidant components are gaining popularity as a result of their efficacy in enhancing human health and nutrition [ 3 , 4 ]. They have been linked to lower cancer and heart disease incidence and in turn the mortality rates [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%